Ni-Mn-Sn: novel ferromagnetic shape memory alloys - Khovaylo, V.; Koledov, V.; Novosad, V.; Korolyov, A.; Ohtsuka, M.; Saveleva, O.; Takagi, T.; Shavroov, V. (Functional Materials, 2006)
Two series of novel ferromagnetic shape memory alloys, Ni₅₀₊ₓMn₃₇₋ₓSn₁₃ and Ni₅₀₊ᵧNm₃₉₋ᵧSn₁₁ were characterized by differential scanning calorimetry and magnetization measurements. The results obtained showed that the substitution of Mn for Ni results in an increase of martensitic transformation temperature Tm. The trend to Tm increase is not observed in the alloys with x, y > 2 at %. The results of magnetization measurements evidence complex magnetic properties of these compounds.